Aktywność inwestorów w procesach fuzji i przejęć banków komercyjnychw polskim sektorze bankowym - Korzeb, Zbigniew (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The objective of the study is to analyse periodicity of mergers and acquisitionsof commercial banks in the Polish banking sector. The research concentrates onbehaviour of strategic investors in this type of investment operations after 1989.The findings of the analysis do not support the thesis about periodicity of mergersand acquisitions in the Polish banking sector. The only element that standsout is the financial crisis caused by subprime credits. There is no doubt that theevents of September and October 2008 are responsible for the complete lack oftransactions in the sector in that year.